Integrasi Analisis PESTEL dan Akuntansi Manajemen Lingkungan dalam Strategi Manufaktur Hijau - Satria Yudhia Wijaya; Tiolina Evi Nausta Pardede (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Sustainability transformation has become an increasingly important issue for manufacturing firms, particularly in response to growing environmental pressures and changing stakeholder expectations. While prior studies have widely examined sustainability practices and firm performance, relatively limited attention has been given to how external environmental pressures are translated into internal strategic actions. This study addresses that gap by proposing a conceptual framework that integrates PESTEL analysis and Environmental Management Accounting (EMA) in explaining the development of green manufacturing strategy and its implications for sustainable performance. Based on institutional theory and the resource-based view, this study adopts a conceptual approach based on a systematic literature review. The analysis suggests that PESTEL factors operate as multidimensional external pressures that encourage firms to pursue sustainability transformation. However, these pressures do not automatically lead to improved performance outcomes. Instead, firms require internal organizational capabilities that enable environmental information to be interpreted and incorporated into strategic decision-making processes. In this context, EMA is positioned as a mediating capability that supports the implementation of green manufacturing strategy.